Permanent price impact asymmetry of trades with institutional constraints - CHIYACHANTANA, Chiraphol N. (Institutional Knowledge at Singapore Management University, 2017)
Dynamic institutional trading constraints related to capital, diversification, and short-selling asymmetrically affect the incorporation of new information as reflected in the permanent price impact of their trades. The sign of the permanent price impact asymmetry between institutional buys versus sells is positive at the initial stage of a price run-up and reverses due to changing constraints with a prolonged price run-up in a stock. Idiosyncratic volatility, analyst forecast dispersion, trading intensity, price dispersion, and bullish market conditions further sharpen the initial asymmetry, as well as its reversal after a price run-up.